A Digital Currency Architecture for Privacy and Owner-Custodianship - G. Goodel; H. D. Al-Nakib; P. Tasca (Russian Journal of Economics and Law, 2021)
Objective: to present the new approach to perform monetary transactions with digital currency.Methods: abstract-logical, analytical methods.Results: in recent years, electronic retail payment mechanisms, especially e-commerce and card payments at the point of sale, have increasingly replaced cash in many developed countries. As a result, societies are losing a critical public retail payment option, and retail consumers are losing important rights associated with using cash. To address this concern, we propose an approach to digital currency that would allow people without banking relationships to transact electronically and privately, including both e-commerce purchases and point-of-sale purchases that are required to be cashless.The article shows the advantages of cash payments compared to non-cash ones and defines the possibility to transform these advantages into the central bank digital currencies. The disputable issues of commercial banks development under the spread of digital currencies are discussed. The architecture of digital currencies is described, including distributed ledgers technology. It was shown that, for the digital currency to function effectively, it is necessary to include the privacy of end-users into its architecture; measures to achieve that are determined.Scientific novelty: the approached proposed in the article should be used to develop the digital currencies infrastructure. It should be government-backed, privately-operated and ensure that every transaction is registered by a bank or money services business, relying upon non-custodial wallets backed by privacy-enhancing technology, such as blind signatures or zero-knowledge proofs, to ensure that transaction counterparties are not revealed. This approach can also facilitate more efficient and transparent clearing, settlement, and management of systemic risk. We argue that our system can restore and preserve the salient features of cash, including privacy, owner-custodianship, fungibility, and accessibility, while also preserving fractional reserve banking and the existing two-tiered banking system.Practical significance: the proposed approach can be applied in the practical organization of perform monetary transactions using digital currencies.The article was first published in English language by Future Internet. For more information please contact the editorial office.For original publication: Goodell G., Al-Nakib H. D., Tasca P. A Digital Currency Architecture for Privacy and Owner-Custodianship, Future Internet, 2021, 13, 130. https://doi.org/10.3390/fi13050130Publication URL: https://www.mdpi.com/1999-5903/13/5/130